Main bioactive phenolic compounds in marine algae and their mechanisms of action supporting potential health benefits - Jiménez López, Cecília (2018)
Given the growing tendency of consumers to choose products with natural ingredients, food industries have directed scientific research in this direction. In this regard, algae are an attractive option for the research, since they can synthesize a group of secondary metabolites, called phenolic compounds, associated with really promising properties and bioactivities. The objective of this work was to classify the major phenolic compounds, compare the effectiveness of the different extractive techniques used for their extraction, from traditional systems (like heat assisted extraction) to the most advance ones (such as ultrasound, microwave or supercritical fluid extraction); the available methods for identification and quantification; the stability of the enriched extract in phenolic compounds and the main bioactivities described for these secondary metabolites, to offer an overview of the situation to consider if it is possible and/or convenient an orientation of phenolic compounds from algae towards an industrial application.